2019
DOI: 10.1093/pasj/psz065
|View full text |Cite
|
Sign up to set email alerts
|

Nobeyama 45 m mapping observations toward Orion A. II. Classification of cloud structures and variation of the 13CO/C18O abundance ratio due to far-UV radiation

Abstract: We present results of the classification of cloud structures toward the Orion A Giant Molecular Cloud based on wide-field 12 CO (J = 1-0), 13 CO (J = 1-0), and C 18 O (J = 1-0) observations using the Nobeyama 45 m radio telescope. We identified 78 clouds toward Orion A by applying Spectral Clustering for Interstellar Molecular Emission Segmentation (SCIMES) to the data cube of the column density of 13 CO. Well-known subregions such as OMC-1, OMC-2/3, OMC-4, OMC-5, NGC 1977, L1641-N, and the dark lane south fil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 63 publications
(84 reference statements)
2
19
0
Order By: Relevance
“…proposed that FUV radiation can photodissociate HNC more than HCN (photodissociation cross sections larger for HNC), leading to higher HCN/HNC ratios for stronger FUV. However, Nakamura et al (2019) found a HCN/HNC ratio lower towards the region VLA 13 (a protostar nearby FIR4) than in the N 2 H + clump. Thus, since VLA 13 shows a FUV radiation strength 140 times larger than the N 2 H + clump of FIR4 (Ishii et al 2019), they concluded that the effect of a temperature higher than 24 K is the main responsible for the observed HCN/HNC ratios.…”
Section: The Hcn/hnc Ratiomentioning
confidence: 74%
“…proposed that FUV radiation can photodissociate HNC more than HCN (photodissociation cross sections larger for HNC), leading to higher HCN/HNC ratios for stronger FUV. However, Nakamura et al (2019) found a HCN/HNC ratio lower towards the region VLA 13 (a protostar nearby FIR4) than in the N 2 H + clump. Thus, since VLA 13 shows a FUV radiation strength 140 times larger than the N 2 H + clump of FIR4 (Ishii et al 2019), they concluded that the effect of a temperature higher than 24 K is the main responsible for the observed HCN/HNC ratios.…”
Section: The Hcn/hnc Ratiomentioning
confidence: 74%
“…The 12 CO J=1-0 and 13 CO J=1-0 observations of Orion A were carried out from 2007 to 2017 by the Nobeyama Radio Observatory 45 m telescope (NRO 45m), using two different receivers (Shimajiri et al 2015a,b;Ishii et al 2019;Nakamura et al 2019). The two maps were calibrated to the same intensity scale and combined on a common grid with a pixel scale of 7 .5, which corresponds to an effective angular resolution of 22 .…”
Section: Nro45 Orion Surveymentioning
confidence: 99%
“…The two maps were calibrated to the same intensity scale and combined on a common grid with a pixel scale of 7 .5, which corresponds to an effective angular resolution of 22 . Ishii et al (2019) smoothed the combined map to a velocity resolution of 0.22 km/s, and further converted the intensity to the main beam temperature scale that is benchmarked with data from FCRAO and IRAM 30m. The final sensitivity for the 12 CO map is 0.35 K, while the sensitivity for the 13 CO map is 0.40 K. The velocity range of the Orion data spans -2.9 to 19.3 km s −1 .…”
Section: Nro45 Orion Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…In order to reveal physical properties of the clouds and interactions between stars and ISM, there have been a number of observations in various wavelengths. Observations in the millimeter-wavelengths toward Orion A revealed the distributions and properties of the interstellar molecular gas leading to star formation (e.g., Nishimura et al 2015;Nakamura et al 2019;Ishii et al 2019), and distributions and proper motions of young stars around Orion A have been widely studied in the optical wavelengths (e.g., Kounkel et al 2018;Zari et al 2019).…”
Section: Introductionmentioning
confidence: 99%